Antithrombotic and Antioxidant Activities of Binahong [Anredera cordifolia (Ten.) Steenis] Leaf Ethanol Extract and Its Nanoemulsion Preparation in Swiss Webster Mice - Maria Immaculata Iwo; Amirah Adlia; Silviyanita Isna Septila; Yennie Agnes Pratama; Dicki Bakhtiar Purkon (Journal of Tropical Pharmacy and Chemistry, 2022)
Platelet aggregation has the potential to form thrombi and result in cardiovascular system diseases such as myocardial infarction and ischemic stroke - one of the leading causes of death globally. Traditionally, people use binahong leaves as blood thinners. Therefore, this study aims to obtain scientific data on the efficacy of binahong leaf as antithrombotic. The efficacy test was carried out on male Swiss-Webster mice. The results showed that the ethanol extract of binahong leaves at doses of 50 (BLEE50) and 100 mg/kg bw (BLEE100) could increase bleeding time on H7 (7.61±1.79% and 3.72±1.76% vs 1.08±0.90%) and H14 (13.81±4.42% and 5.06±2.30% vs 1.66±1.09%) and coagulation time at H7 (5.01±1.36% and 4.18±1.67% vs 1.38±1.08%) and at H14 (7.92±1.97% and 7.19±1.96% vs 1.70±1.10%) significantly (p<0.05). The two doses of BLEE were formulated in the form of nanoemulsions with the Self Nano Emulsifying Drug Delivery System (NBLEE50 and NBLEE100) were also able to prolong bleeding time and coagulation time significantly (p<0.01) but only NBLEE50 prolonged bleeding time (p<0.05) significantly against BLEE50. In the test of the anti-platelet aggregation effect with ADP as an inducer, both doses of BLEE and the nanoemulsion preparation (NBLEE) could significantly (p<0.01) inhibit platelet aggregation with a percentage of inhibition >70% which was not different from the standard (acetylsalicylic acid). In the antioxidant effect test using the DPPH method, BLEE has an IC50 = 66.08?g/mL which is classified as a strong antioxidant. Both doses of BLEE and its NBLEE could significantly (p<0.01) inhibit lipid peroxidation in plasma and liver and NO radicals formation. BLEE50 can significantly (p<0.05) reduce mean platelet volume (6.05±0.24fL vs 6.55±0.34fL) and platelet distribution width (8.52±0.36% vs 9.25±0.42%). Based on those results, BLEE has the potential to be used as an antiplatelet aggregation and antioxidant.